Pengaruh Inklusi Keuangan dan Payment Gateway terhadap Kinerja Keuangan UMKM di Kota Denpasar dengan Literasi Keuangan sebagai Variabel Moderasi - Ni Putu Puja Ardiana Reswari; I Made Suidarma (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study examines the effect of financial inclusion and payment gateway usage on the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in Denpasar City, with financial literacy as a moderating variable. A quantitative survey was conducted using questionnaires distributed to MSME owners who use formal financial services and digital payment instruments, and the data were analyzed with PLS-SEM using SmartPLS 4.0. The results show that both financial inclusion and payment gateway usage have a positive and significant impact on MSME financial performance, while financial literacy strengthens these relationships by enabling business owners to manage and optimize the use of financial products and digital payment systems more effectively. The study concludes that expanding access to financial services, encouraging the adoption of payment gateways, and improving financial literacy are essential strategies to enhance MSME financial performance in the digital era and offer useful insights for policymakers, financial institutions, and MSME stakeholders.